Absence of P2Y2 Receptor Does Not Prevent Bone Destruction in a Murine Model of Muscle Paralysis-Induced Bone Loss - Agrawal, Ankita; Ellegaard, Maria; Haanes, Kristian Agmund; Wang, Ning; Gartland, Alison; Ding, Ming; Praetorius, Helle; Jørgensen, Niklas Rye (Frontiers in Endocrinology, 2022)
Increased incidence of bone fractures in the elderly is associated with gradual sarcopenia. Similar deterioration of bone quality is seen with prolonged bed rest, spinal cord injuries or in astronauts exposed to microgravity and, preceded by loss of muscle mass. Signaling mechanisms involving uridine-5′-triphosphate (UTP) regulate bone homeostasis via P2Y2 receptors on osteoblasts and osteoclasts, whilst dictating the bone cells’ response to mechanical loading. We hypothesized that muscle paralysis-induced loss of bone quality would be prevented in P2Y2 receptor knockout (KO) mice. Female mice injected with botulinum toxin (BTX) in the hind limb developed muscle paralysis and femoral DXA analysis showed reduction in bone mineral density (<10%), bone mineral content (<16%) and bone area (<6%) in wildtype (WT) and KO littermates (<13%, <21%, <9% respectively). The femoral metaphyseal strength was reduced equally in both KO and WT (<37%) and <11% in diaphysis region of KO, compared to the saline injected controls. Tibial micro-CT showed reduced cortical thickness (12% in WT vs. 9% in KO), trabecular bone volume (38% in both WT and KO) trabecular thickness (22% in WT vs. 27% in KO) and increased SMI (26% in WT vs. 19% in KO) after BTX. Tibial histomorphometry showed reduced formation in KO (16%) but unchanged resorption in both WT and KO. Furthermore, analyses of DXA and bone strength after regaining the muscle function showed partial bone recovery in the KO and no difference in the recovery compared to the WT mice. Primary osteoblasts from KO mice displayed increased viability and alkaline phosphatase activity but, impaired bone nodule formation. Significantly more TRAP-positive osteoclasts were generated from KO mice but displayed reduced resorptive function. Our data showed that hind limb paralysis with a single dose of BTX caused profound bone loss after 3 weeks, and an incomplete reversal of bone loss by week 19. Our findings indicate no role of the P2Y2 receptor in the bone loss after a period of skeletal unloading in mice or, in the bone recovery after restoration of muscle function.